Finite Element Model of Machining with High Pressure Coolant for Ti- 6Al-4V alloy - Abu Bakar, Mohd Hadzley; Raja Abdullah, Raja Izamshah; Ahmad, Siti Sarah Madia; Mohamad Raffi, Nurul Fatin (Elsevier, 2013)
This study present a series of finite element models for high-pressure jet-assisted machining of Ti-6Al-4V alloy. The application of Fluid- Structure Interaction (FSI) together with the Johnson-Cook plasticity model, Cockcroft-Latham chip separation criteria and EOS polynomial were implemented to study the effect of coolant pressure on chip formation, cutting force and cutting temperature. The resulting motion of fluid at the tool-chip interface, chip breakage, cutting force as well as temperature generation at the tool-chip interfaceis then interpreted, analyzed and compared to their real experimental results. The models simulate interactions between the fluid and solid structure, where continuous chip formation was observed when simulation in conventional coolant supply while chip breakage was clearly evident as high-pressure coolant was introduced. Increasing coolant pressure significantly reduce the friction at the tool-chip interface, which significantly reduced the cutting force and cutting temperature.